Wood Ash Induced pH Changes Strongly Affect Soil Bacterial Numbers and Community Composition - Bang-Andreasen, Toke; Nielsen, Jeppe T.; Voriskova, Jana; Heise, Janine; Rønn, Regin; Kjøller, Rasmus; Hansen, Hans C. B.; Jacobsen, Carsten S. (Frontiers in Microbiology, 2017)
Recirculation of wood ash from energy production to forest soil improves the sustainability of this energy production form as recycled wood ash contains nutrients that otherwise would be lost at harvest. In addition, wood-ash is beneficial to many soils due to its inherent acid-neutralizing capabilities. However, wood ash has several ecosystem-perturbing effects like increased soil pH and pore water electrical conductivity both known to strongly impact soil bacterial numbers and community composition. Studies investigating soil bacterial community responses to wood ash application remain sparse and the available results are ambiguous and remain at a general taxonomic level. Here we investigate the response of bacterial communities in a spruce forest soil to wood ash addition corresponding to 0, 5, 22 and 167 t wood ash ha-1. We used culture-based enumerations of general bacteria, Pseudomonas and sporeforming bacteria combined with 16S rRNA gene amplicon sequencing to valuate soil bacterial responses to wood ash application. Results showed that wood ash addition strongly increased soil pH and electrical conductivity. Soil pH increased from acidic through neutral at 22 t ha-1 to alkaline at 167 t ha-1. Bacterial numbers significantly increased up to a wood ash dose of 22 t ha-1 followed by significant decrease at 167 t ha-1 wood ash. The soil bacterial community composition changed after wood ash application with copiotrophic bacteria responding positively up to a wood ash dose of 22 t ha-1 while the adverse effect was seen for oligotrophic bacteria. Marked changes in bacterial community composition occurred at a wood ash dose of 167 t ha-1 with a single alkaliphilic genus dominating. Additionally, spore-formers became abundant at an ash dose of 167 t ha-1 whereas this was not the case at lower ash doses. Lastly, bacterial richness and diversity strongly decreased with increasing amount of wood ash applied. All of the observed bacterial responses can be directly explained by the wood ash induced changes in pH, electrical conductivity and the addition of wood ash inherent nutrients.